1,6-Conjugate addition of in situ generated aryldiazenes to p-quinone methides - Mamale, Ajay G.; Paul, Sayantan; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2024)
Herein we report a transition-metal free, base-mediated 1,6-conjugate addition of aryldiazenes to para-quinone methides (p-QMs). Arylhydrazines were used for the in situ generation of aryldiazenes using a base-mediated protocol in the presence of air as the oxidant. The 1,6-conjugate addition of aryldiazenes to para-quinone methides via a radical mechanism is followed by an oxidative rearrangement to furnish the desired product, arylhydrazones. Interestingly, our synthetic protocol results in the formation of an aryldiazene radical, which undergoes 1,6-conjugate addition with p-QMs to furnish the arylhydrazones.

Methanesulfonic acid-catalyzed friedel-crafts alkylation: towards sustainable synthesis of arylalkanes from donor-acceptor cyclopropane ketones - Goswami, Lakshmi; Paul, Sayantan; Mamale, Ajay G.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2024)
We present herein Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane ketones. The presence of the 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules inspired us to pursue the direct synthesis of these structural frameworks. Utilizing methanesulfonic acid (MeSO3H) as a catalyst, we achieved a more environmentally friendly and high-yielding synthesis, owing to its cost-effectiveness, biodegradability, transition-metal and additives free conditions. Furthermore, we have successfully extended our developed methodology to thiophenols, resulting in the production of sulfur-based butan-1-one derivatives in good yields. The presence of 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules prompted us to develop a Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane. image
Keywords: donor-acceptor cyclopropane; Friedel-Crafts alkylation; methanesulfonic acid; Phenols; thiophenol

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.